A Study of Factors Affecting Price Forecasting in the Pork Supply Chain in Thailand - Kiattiteerachai, Pimchanok; Khongmalai, Orapan (Suan Dusit Graduate School Academic Journal, 2023)
This research was quantitative research which aimed to study the factors affecting price forecasting of products in the pork supply chain in Thailand. In addition, it aimed to study the guidelines for the price forecasting of products through the quantitative research process by collecting secondary data for the past 10 years, over the period 2011 - 2021 published by relevant government agencies in Thailand and analyzed by Multiple Linear Regressions. The findings revealed that, first, the pig prices, retail diesel prices and Consumer Price Index can explain pork price at 92.7%. Second, cost of pigs, such as feed ingredients and piglet prices can explain pig prices variation at 80.3%, except soybeans meal price. Third, volume of imports and exports of agricultural products, as well as retail diesel prices, can explain piglet price, rice C1 price, soybean meal prices, corn prices, and extracted rice bran oil price at 19.3%, 31.5%, 19.4%, 21.2% and 7.30%, respectively. The Multiple Linear Regression Equation was found to predict the price quite accurately when compared to the actual price, except piglet prices and rice C1 prices. However, there were other factors that affected changes in the price structure, such as weather conditions, disasters, exchange rates and political situations that required further study for efficient decision making and cost management.